Rancang Bangun Alat Penyapu Lantai Semi Mekanik untuk Kampus Universitas Muhammadiyah (UM) Sumbar - Firman Sandhy; Armila Armila; Rudi Kurniawan Arief (Politeknik Negeri Padang, 2022)
Sweeping the floor is not a hard job, sweeping activities will be hard and take up a lot of time if the area to be worked on is very large like in UM-West Sumatra. To simplify and save time, it is necessary to innovate a floor sweeper. The push system floor sweeper is a form of innovation that facilitates the process of sweeping the floor. In this study a thrust system floor sweeper was designed and manufactured. The design process begins with identification of needs, concept design, design and analysis using the fabrication method, then this tool is tested in a room of 35.28 meters, 61.2 meters and 122.4 meters. From the trials conducted, it was found that the floor sweeper functions properly and can clean large and spacious rooms with 50% efficiency. Thus it can be concluded that a floor sweeper can simplify the process of sweeping the floor by 50% compared to an ordinary broom.